If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 8x + -6 Reorder the terms: 7x = -6 + 8x Solving 7x = -6 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 7x + -8x = -6 + 8x + -8x Combine like terms: 7x + -8x = -1x -1x = -6 + 8x + -8x Combine like terms: 8x + -8x = 0 -1x = -6 + 0 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 14-2x=2(7-x) | | 45x-36y=180 | | -37=-1+3(3n-3) | | x^3+x^2-56x=0 | | x^2+4x+17= | | -36=-1+3(3n-3) | | 5x+2=x+(2x-10) | | .6u+2=6 | | Y=16+.4(62) | | 2x^2+2x=-8x-12 | | 2x-1=-7x-1 | | -27-x^2=0 | | (-80)+33= | | 2(x+3)-4(x+9)=6(x+7) | | -3(3-3a)=-36 | | Y=16+.4(x) | | x-.2x=120 | | 92=16+.4(x) | | 6=3b+3b | | 5x-18=8z | | 4(x-3)-5(x+7)+8(x-4)=3(2x+1)-7(x-9) | | 121x^2-1= | | 6y^2+8y+2=0 | | -3x+2=-4x+12 | | 55-11n=0 | | 5(k-4)=4-4k | | 5x^2+15x-270=0 | | 11-19x-6x^2= | | 3n-42=-7(2-3n)+8 | | 16x+3=12x-17 | | 21y^2-3y+2= | | 8x-(2x+1)=3x-13 |